2020
DOI: 10.3389/fchem.2020.00482
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Zeolitic Materials (MZMs) Derived From Zeolite Y Using a Microwave Method for Catalysis

Abstract: Mesostructured zeolitic materials (MZMs) with relatively high acidity in comparison with the mesoporous siliceous MCM-41 were prepared via an efficient, mild, and simple post-synthetic treatment of Y zeolite facilitated by microwave irradiation, i.e., microwave-assisted chelation (MWAC). The disordered mesoporous aluminosilicates materials (DMASs) of MZM were created from Y zeolite in the absence of using mesoscale templates. The prepared DMASs showed the good mesoporous features with the mesopore area and vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 66 publications
(88 reference statements)
0
12
0
Order By: Relevance
“…Additionally, MW-assisted post-synthetic modification of zeolites and zeotypes (in the liquid-phase) regarding the acidity [21][22][23][24] and porosity [25][26][27][28] was also attempted using the mineral acids and bases. Especially, our recent work has shown that the combination of chelation dealumination with the microwave irradiation was highly efficient to prepare mesoporous zeolitic materials [29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, MW-assisted post-synthetic modification of zeolites and zeotypes (in the liquid-phase) regarding the acidity [21][22][23][24] and porosity [25][26][27][28] was also attempted using the mineral acids and bases. Especially, our recent work has shown that the combination of chelation dealumination with the microwave irradiation was highly efficient to prepare mesoporous zeolitic materials [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Here we report the extended investigation of the post-synthetic treatment protocol involving chelation dealumination under MW irradiation (i.e., MW-Assisted Chelation, MWAC [29,30]) for producing the modified synthetic zeolites with hierarchical pore structures. Specifically, and significantly, the MWAC method has enabled the preparation of hierarchical FAU zeolite Y on the minute timescale, and the obtained Y zeolites show exceptional hierarchical mesoporous features with the specific external surface area (Sext.)…”
Section: Introductionmentioning
confidence: 99%
“…This proves that the MWAC method is a time-(and cost-) effective method, which may be classified as environmentally friendly and sustainable. [297] Top-Down Methods-Desilication: Like previously mentioned, a dealumination step may be required previous to desilication to remove protective Al species. Starting with a publication from Li et al, this group performed such an alkaline treatment that was preceded by two dealumination steps: I) a steam treatment and II) an acid treatment (e.g., fluorosilicic acid, HCl).…”
Section: Zeolite Ymentioning
confidence: 99%
“…This proves that the MWAC method is a time‐ (and cost‐) effective method, which may be classified as environmentally friendly and sustainable. [ 297 ]…”
Section: Synthesis Of Hierarchical 12‐mr Zeolitesmentioning
confidence: 99%
“…One major drawback of zeolites is their microporous nature, which can hinder mass diffusion leading to coking and reduced in-pore diffusion of substrates. Incorporating complementary secondary porosity, either mesopores or macropores, has been demonstrated to help alleviate coking during gas-phase reactions [18][19][20]. It also can impart beneficial attributes to liquid-phase reactions through increased accessibility of active sites [21].…”
Section: Introductionmentioning
confidence: 99%